Penyuluhan UMKM Go Ekspor (Strategi Jualan Online Di Pasar Internasional) Pada Pelaku UMKM di Desa Gerogol Lombok Barat - Rusdi; Armiani; Ni Nyoman Yuliati; Sukma Hidayat Kurnia Abadi; I Made Suardana; Endang Kartini; Baiq Kisnawati; Khaerul Hadi; Surahman Hidayat; Ulfiyani Asdiansyuri; Faizatul Fajariah (Valid Jurnal Pengabdian, 2025)
This community service aims to provide education to MSME actors related to Online Selling Strategies in the International Market so that there is added value and profitability for MSME business actors in Gerogol Village. The target of service is MSME actors who are registered and already have a business license in Gerogol Village. Problems are solved in three stages of activities, namely preparation, implementation and evaluation. Preparations were made by conducting preliminary interviews to find out the conditions in the field regarding the basic problem of non-development of MSMEs in Gerogol Village. The implementation was carried out by providing counseling on how to create added value for the businesses of each MSME actor in Gerogol Village. Evaluation of activities is carried out for each stage by collecting and concluding data from each stage of the activity. The results of the Online Sales Strategy in the International Market counseling activity for MSMEs in Grogol Village, West Lombok, show a high level of enthusiasm from MSME actors because there are new opportunities to increase business scale and profits.